Regulalatory specifics of development of descending thoracic aortic aneurysms at the place of repair of coarctation - Dykukha, S. O.; Kravchenko, I. M.; Tarasenko, Yu. M.; Kravchenko, V. I.; Cherpak, B. V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The work is dedicated to the analysis of aneurysms of the descending thoracic aorta, which developed as a consequence of surgical treatment of aortic coarctation. It is shown that the frequency of aortic aneurysms at the site of repair of coarctation, their dependence on the development of methods of correction of coarctation of the aorta, the pathogenesis of the development, and especially the attention for their timely diagnosis and treatment.